PERBANDINGAN METODE SAW DAN TOPSIS DALAM PEMILIHAN FASILITAS DI RANOH ISLAND - Mulyadi, Yandy Sasanaputra; Mesri Silalahi (Computer Science and Industrial Engineering, 2024)
This research focuses on the selection of facilities at Ranoh Island, a tourist destination at Jembatan 6, Jl. Trans Barelang, Galang, Batam City, Riau Islands, which has experienced an increase in visits every year. Despite having ample facilities, Ranoh Island aims to ensure a gratifying tourist experience. However, a lack of clear guidance in facility selection can lead to inefficient decisions, negatively impacting the overall tourist experience. The research employs multi-criteria decision-making methods, specifically comparing Simple Additive Weighting (SAW) and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). Data from tourist visits over the past three months, including visitor satisfaction with facilities, were analyzed. Results indicate that the SAW method yields a higher final score than TOPSIS, each having its own strengths and weaknesses. The study emphasizes the importance of choosing an appropriate decision-making method; SAW is suitable for situations where preference weights can be flexibly set, while TOPSIS is preferable for finding the best solution from alternatives. The findings offer valuable insights for decision-makers on Ranoh Island to enhance facilities, improve the tourist experience, and foster tourism growth.